Mengapa Kekuatan Sinyal Tidak Selalu Menjamin Kualitas Komunikasi - Nalendri Nabiwa; Rustamaji . (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Signal strength is often considered the primary indicator of communication quality. However, in practice, a strong signal condition does not always result in good communication performance. This study aims to explain the relationship between signal strength and communication quality based on telecommunication system parameters, namely amplitude, frequency, bandwidth, and the presence of noise. The method used is a literature review of textbooks and international journals published from 2020 onwards. The results of the review indicate that communication quality is the outcome of overall system performance. Frequency mismatch, bandwidth limitations, and noise dominance can degrade information quality even when the signal is received with high strength. Therefore, signal strength is not the sole determinant of communication quality.